Kedudukan Anak Perempuan Dalam Pembagian Waris Suku Batak Toba Ditinjau Dari Hukum Adat - Nadia Prasista Maharani; Achmad Arifai Sidik (Universitas Sains dan Teknologi Komputer, 2024)
The country of Indonesia consists of various islands so it has many kinds of tribes and customs within it. Customary law in Indonesia was born from customary needs that arise from within society. Without realizing it, customary law is able to provide answers to all the problems that exist in everyday life. The implementation of existing laws in Indonesia has never been separated from the current existence of customary law. One of the traditional tribes that applies customary law habits is the Batak tribe, especially in terms of the traditional inheritance distribution system. The traditional inheritance system in the Batak region is patrilineal inheritance where children will inherit from their father provided that the son will receive the inheritance, so that daughters are considered to have no rights to inheritance. The inequality felt by girls creates conflict in the surrounding community so that customary law is considered not fully applicable.